Encapsulated Textile Organic Solar Cells Fabricated by Spray Coating. Issue 1 (9th January 2019) - Li, Yi; Arumugam, Sasikumar; Krishnan, Chirenjeevi; Charlton, Martin D. B.; Beeby, Stephen P.
Abstract: Solution based processes such as screen printing and spray coating are established processes for fabricating organic solar cells (OSCs) on flexible polymer substrates. However, realizing a flexible solar cell on a textile substrate remains a significant challenge due to the properties of the textile itself, which can present an absorbent, rough and fibrous surface. The textile also limits processing temperatures which can reduce functional materials performance. In this work, we demonstrate an optimized fabrication approach using entirely spray coating to fabricate textile OSCs with a power conversion efficiency (PCE) of 0.4 %. An interface layer is first deposited on the standard woven textile that forms a smooth supporting layer for the subsequent spray coated functional layers. A top encapsulation layer is deposited on top of the fabricated textile OSCs, which improves the durability and life time of the OSCs is evidenced by cyclic bending test. Abstract : A fully spray coated organic solar cell fabricated directly on to standard polyester cotton fabric demonstrates an efficiency of 0.4%. A flexible interface layer smooths the fabric surface, subsequent functional films are deposited by spray coating and encapsulated to increase the lifetime and durability of the cells. Processes performed in a nitrogen environment and temperatures limited to 150 o C. This approach can fabricate solar cells on any textiles.